2018
DOI: 10.3892/ol.2018.8929
|View full text |Cite
|
Sign up to set email alerts
|

Arginine methyltransferase inhibitor‑1 inhibits sarcoma viability in�vitro and in�vivo

Abstract: Protein arginine methyltransferases (PRMTs) are a class of epigenetic modified enzymes that are overexpressed in a various types of cancer and serve pivotal functions in malignant transformation. Arginine methyltransferase inhibitor-1 (AMI-1) is a symmetrical sulfonated urea that inhibits the activity of type I PRMT in vitro. However, previous studies demonstrated that AMI-1 may also inhibit the activity of type II PRMT5 in vitro. To the best of our knowledge, the present study provides the first evidence that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Blocking PRMT activity in many tumours has proven to be an effective way to induce apoptosis in transformed cells of osteosarcoma, colorectal cancer, lung cancer and melanoma [ 29 , 49 , 53 , 54 ]. We have shown that AMI-1 and SAH significantly affect the level of histone arginine methylation at H3R2me2a, H3R8me2s, H3R17me2a, H4R3me2a ( Figure 5 ) In our study, we observed that the use of AMI-1 and SAH in RMS cells also resulted in a statistically significant increase in apoptosis ( Figure 3 B).…”
Section: Discussionmentioning
confidence: 99%
“…Blocking PRMT activity in many tumours has proven to be an effective way to induce apoptosis in transformed cells of osteosarcoma, colorectal cancer, lung cancer and melanoma [ 29 , 49 , 53 , 54 ]. We have shown that AMI-1 and SAH significantly affect the level of histone arginine methylation at H3R2me2a, H3R8me2s, H3R17me2a, H4R3me2a ( Figure 5 ) In our study, we observed that the use of AMI-1 and SAH in RMS cells also resulted in a statistically significant increase in apoptosis ( Figure 3 B).…”
Section: Discussionmentioning
confidence: 99%
“…Initially, AMI-1 was used to inhibit type I PRMTs (PRMT1- PRMT4, PRMT6, and PRMT8) in vitro [ 17 ]. However, further studies showed that the effect of AMI-1 on suppressing the proliferation of solid tumors (e.g., hepatocellular carcinoma, colorectal cancer, and gastric cancer) is mediated by inhibiting type II PRMT5 [ 26 , 27 ]. Most studies that exploited the anti-tumor potential of AMI-1 by targeting PRMT5 used a high dose of AMI-1 (in the mM range) [ 26 , 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the limitations of our study is that the effect of targeting PRMT1 by AMI-1 was not investigated. However, previous studies showed that the anti-tumor effect of AMI-1 is rather mediated through PRMT5 [ 26 , 27 ]. Another limitation is to precisely define the subcellular localization of PRMT5, which requires nuclear extraction.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we find that sole deletion of PRMT5 in T cells is sufficient to halt multiple aspects of severe lung inflammation. It is important to note that, at least in T cells, PRMT5 has been found to regulate PRMT1 in a positive feedback loop (27)(28)(29)(30). Therefore, part of PRMT5's effects could be indirectly mediated by PRMT1 induction.…”
Section: Discussionmentioning
confidence: 99%